Students’ intention to educational loan repayment in UiTM Cawangan Melaka Kampus Bandaraya Melaka / Noorfarhany Abdul Rashid - Abdul Rashid, Noorfarhany (Faculty of Business and Management, 2018)
The title of this project paper is “Students’ Intention to Educational Loan Repayment in Uitm Cawangan Melaka Kampus Bandaraya.”Three independent variables are identified that influenced students’ intention to educational loan repayment which are Media Awareness, Parental Influence and Perceptions that Loan Agreement Affects the Quality of Life. In order to complete this project paper, three hypotheses are constructed that mainly focused in determining the influence of the independent variables towards dependent variable. The sample size obtained is 318 respondents out of 1724 of the total population in UiTM Cawangan Melaka Kampus Bandaraya by using convenience sampling method. Primary data collection method is used by the researcher which is distributing questionnaire to the respondents. All the data obtained is analyzed using normality test, reliability test, frequency testing, descriptive statistical test, Pearson Correlation coefficient, and regression testing.